Problematika Pendidikan Dalam Proses Pembelajaran Di Lembaga Raudhatul Athfal - Erna Budiarti; Lubna Aljufry; Durrotul M.A; Sri Juani Purwaningsih; Hera Gustina (Jurnal Pendidikan Indonesia, 2023)
Institutions that have a significant role in educating early childhood, one of which is the educational institution of RA kec. Sumberbaru kab. jember east java. this institution is a basic institution that is under the auspices of the ministry of religion which is intended for children aged 5-6 years. this level of education has a very important role in developing the abilities or potential possessed by early childhood. the potential or abilities that must be developed are six namely cognitive abilities, physical motoric, language, social emotional, art and religious and moral values. in this study used a qualitative approach, with the type of field research. To collect this data using observation, interview, and documentation methods. From the data collected, it will then be analyzed using reflective descriptive analysis techniques, data validity using source triagulation. if these potentials can be developed, the goal is that policy makers need to make improvements to the system that is easier, simpler and more efficient so as not to interfere with the focus of learning at school. teachers are more focused on educating and providing learning in accordance with parents' expectations. Education is a beacon for everyone and determines a better future. Therefore, there are various problems in education both in the curriculum itself and in resource capacity. Many complaints occur in the field about school leaders and educators who are not good at education management and administration. As well as many educators who perform multiple tasks.